Desain dan Analisis Karakteristik Pegas Koil Sistem Suspensi Belakang untuk Kendaraan Ringan Sepeda Motor Listrik - Bayu Aji Girawan; Joko Setia Pribadi; Nur Akhlis Sarihidaya Laksana (Infotekmesin, 2022)
The vehicle's suspension system have function to reduce vibrations from the shock between the wheels and the road. Previous research discussed the simulation of spring loading with material variations. This research focuses on the design and analysis of springs that will be used in Electric Motorbikes (SEMOLI). Spring analysis between cast stainless steels and carbon stainless steels is done by calculating displacement transmissibility. The analytical method used is the SDOF harmonic method to determine the system response. The results of the analysis are considered for the selection of springs by determining the displacement transmissibility and the response of the suspension system. The results of the analysis of the characteristics of cast stainless steels and carbon stainless steels for active springs 6, 7, and 8 at speeds of 10 km/hour, 20 km/hour, 40 km/hour, 80 km/hour showed a decrease in displacement transmissibility. Characteristics for stainless steel material at steady state condition with active spring 6 is 0.3 second, while 7 and 8 are 0.25 second. The characteristics of overshoot for cast stainless steel material with active spring 6 are 55.3%, 7 are 52.7% and 8 are 50.3%. Stainless steel material has the characteristics of overshoot on active spring 6 is 55.8%, active spring 7 is 53.3%, and active spring 8 is 51 From the characteristic analysis, the best material obtained is cast stainless steel with a smaller displacement value dan good respon.